Enhanced properties of chitosan microparticles over bulk chitosan on the modulation of the auxin signaling pathway with beneficial impacts on root architecture in plants - Iglesias, María José (2019)
Improving the root system architecture (RSA) under adverse environmental conditions by using biostimulants is emerging as a new trait to boost crop productivity. Recently, we have reported the characterization of novel chitosan-based microparticles (CS-MPs) with promising biological properties as rooting agent in lettuce. In this work, we demonstrated that in contrast to bulk chitosan (CS) which exerts root growth inhibition, CS-MPs promoted root growth and development from 1 to 10 µg. ml-1 without cytotoxicity effects at higher doses in Arabidopsis and lettuce seedlings. In addition, we studied the mechanistic mode of action of CS-MPs in the development of early RSA in the Arabidopsis model. CS-MPs unchained an accurate and sustained spatio-temporal activation of the nuclear auxin signaling pathway. Our findings validated a promising scenario for the application of CS-MPs in the modulation of RSA to respond to changing soil environment and improved crop performance.